Two new aphid species of the genus Cryptomyzus Oestlund, 1922 (Hemiptera, Aphididae) from Kazakhstan, and keys to apterous and alate viviparous females - Kadyrbekov, Rustem Kh. (Zootaxa, 2021)
Two new species of the genus Cryptomyzus Oestlund, 1922 are described from Lamiaceae in the Kazakhstan part of West Tien Shan: Cryptomyzus (Cryptomyzus) sairamugamicus sp. n. living on Phlomis salicifolia and C. (C.) karzhantavicus sp. n. living on Stachys betonicifolia. Keys are provided for identification of apterous viviparous females and alate viviparous females of the world’s fauna of the genus Cryptomyzus.